Normality of the Orlicz - Sobolev classes - Ryazanov, V. I.; Salimov, R. R.; Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish a series of new criteria of equicontinuity and, hence, normality of the mappings of Orlicz – Sobolev classes in terms of inner dilatations.